A Multilab Replication of the Ego Depletion Effect. Issue 1 (January 2021) - Dang, Junhua; Barker, Paul; Baumert, Anna; Bentvelzen, Margriet; Berkman, Elliot; Buchholz, Nita; Buczny, Jacek; Chen, Zhansheng; De Cristofaro, Valeria; de Vries, Lianne; Dewitte, Siegfried; Giacomantonio, Mauro; et al.
There is an active debate regarding whether the ego depletion effect is real. A recent preregistered experiment with the Stroop task as the depleting task and the antisaccade task as the outcome task found a medium-level effect size. In the current research, we conducted a preregistered multilab replication of that experiment. Data from 12 labs across the globe ( N = 1, 775) revealed a small and significant ego depletion effect, d = 0.10. After excluding participants who might have responded randomly during the outcome task, the effect size increased to d = 0.16. By adding an informative, unbiased data point to the literature, our findings contribute to clarifying the existence, size, and generality of ego depletion.